Discourse Analysis of Father’s Grassland Mother’s River Based on Register Theory - Hao, Xiaoyuan (Pacific International Journal, 2023)
Based on the framework of register theory, this paper uses the song Father’s Grassland Mother’s River which is collected from the website of wedding poetry as the analysis material. Different linguistic theories to analyze discourses can reveal the linguistic approaches used by the speaker for the realization of speaking intention from the different perspectives. The purpose of this paper is to explore the merits of register theory in the discourse analysis of lyrics and to verify the applicability of register theory in the analysis of lyrics. Though literature research method, quantitative analysis and qualitative analysis, this paper focuses on the register of lyric, including field, tenor, and mode, studying three meta-functions and its meanings of systemic functional linguistics which refers to the field and discussion of ideational function; the tenor and discussion of interpersonal function and the mode and discussion of textual function. The study shows the nationality and musicality of the song, and elucidates the reason for its widely spread among the public. The results of analysis prove that: i) the transitivity, logical relationship and the modal system are all influenced by the vocabularies used in the lyrics; ii) the two kinds of tenor in lyrics reflect the interpersonal relationship; iii) comprehensive analysis of the thematic structure, the information structure and the rhyme and other stylistic characteristics reflects the uniqueness of the lyrics from other types of discourse